Proceedings of the Twenty-Ninth International Joint Conference on Artificial Intelligence 2020
DOI: 10.24963/ijcai.2020/84
|View full text |Cite
|
Sign up to set email alerts
|

SceneEncoder: Scene-Aware Semantic Segmentation of Point Clouds with A Learnable Scene Descriptor

Abstract: Besides local features, global information plays an essential role in semantic segmentation, while recent works usually fail to explicitly extract the meaningful global information and make full use of it. In this paper, we propose a SceneEncoder module to impose a scene-aware guidance to enhance the effect of global information. The module predicts a scene descriptor, which learns to represent the categories of objects existing in the scene and directly guides the point-level semantic segmentation thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Meanwhile, the graph-based method [ 75 , 76 ] uses a graph convolutional operation for point clouds. In addition, some recent studies have shown the importance of global contexts when applying these methods to semantic segmentation tasks [ 77 , 78 , 79 ]. The second limitation is that we cannot handle waveform specific features.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the graph-based method [ 75 , 76 ] uses a graph convolutional operation for point clouds. In addition, some recent studies have shown the importance of global contexts when applying these methods to semantic segmentation tasks [ 77 , 78 , 79 ]. The second limitation is that we cannot handle waveform specific features.…”
Section: Resultsmentioning
confidence: 99%
“…HPEIN [20] extracted features of edges between neighboring points to implicitly model the neighborhood relation. Region similarity loss was proposed to propagate distinguishing features of center points to neighbors with the same categories in a local neighborhood [2].…”
Section: Neighborhood Context Learningmentioning
confidence: 99%
“…As a basic form of 3D data, the point cloud is very popular and can be easily converted into meshes or voxels [1]. Semantic segmentation of point clouds is an essential 3D scene comprehension task yet remains challenging due to its inherent irregularity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the common up-sampling methods using nearest neighbors cannot trace the encoding relationship, thus introducing improper supervisions to the intermediate features (referring Sec 4.4 for discussion). More recently, SceneEncoder [37] provided a method to supervise the center-most layer to extract meaningful global features, but lots of other layers remain unhandled.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by SceneEncoder [37], for each sampled point in any layer of encoder, according to the existence of categories in its receptive field, a multi-hot binary code can be built, designated as target Receptive Field Component Code (RFCC). The target RFCCs at different layers are gen-erated alongside the convolution and down-sampling, thus they can precisely record the existing categories in corresponding receptive fields without any extra annotations.…”
Section: Introductionmentioning
confidence: 99%